SISTEM AUTOMATIC SWITCH REDUNDANT UPS UNTUK BEBAN ESSENSIAL - Markus Dwiyanto Tobi; Alimuddin Mappa (LPPM Poltek ST Paul, 2019)
The role of the power supply device is to produce, process and distribute energy sources. Telecommunication equipment can only operate if it has continuous supply. Therefore, to maintain the continuity of the supply, a UPS (Uninterruptable Power Supply) device system is needed so that the supply to the Essential Load device will remain available so that continuity will be maintained. This research designs and proposes how a series of automatic redundant switch systems on UPS to ensure the availability of power supply for the main equipment of telecommunications systems. The Auto switch circuit is designed to have 3 (three) working stages which will trigger the relay driver as control circuit, namely the normal working condition of the contactor input K1 is present, the input condition is zero (lost), and the input condition is present. This system can automatically supply power to telecommunications equipment.